Change and continuity in Japanese corporate governance - YOSHIKAWA, Toru (Institutional Knowledge at Singapore Management University, 2008)
Previous studies on Japanese corporate governance were largely based on the agency theory framework, and can be seen as attempts to understand the unique monitoring mechanisms in the Japanese context. This paper briefly reviews prior research and then discusses the recent changes in the environment that have been affecting Japanese corporate governance. Our central argument is that there is both change and continuity in Japanese Corporate Governance. We also present emerging research from an institutional theory perspective. In this line of research, corporate governance is treated as part of a nation’s institutional framework and hence, researchers need to understand unique institutional arrangements that affect corporate governance practices and their change or continuity.